Questions for In-Depth Reflection and Improvement of Music Teaching (Appendix to Chapters 50−62) - Kovačič, Bojan (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter offers a series of questions based on the thirteen chapters of the monograph (Chapters 50−62): Overcoming Performance Anxiety, Working with Musically Gifted Students, The Role of Primary School Teachers in Encouraging Students' Musical Creativity through the Planning of School Events, Organising Music Workshops, The Role of Music in Different Cultures, Rhythm and Tempo, Musical Memory, Music and Child Development, Contemporary Dance in Music Education, Music as Therapeutic Tool, Leading a School Choir, Effects of Music on Children's Well-Being and Functioning, and Musical Memory. The questions are divided into four areas (lesson planning, lesson delivery, observation and evaluation, improvement and development) and enable teachers and students to reflect more closely on their own teaching practise.